Elective Labor Induction at 39 Weeks of Gestation Compared With Expectant Management: Factors Associated With Adverse Outcomes in Low-Risk Nulliparous Women. Issue 4 (October 2020) - El-Sayed, Yasser Y.; Rice, Madeline Murguia; Grobman, William A.; Reddy, Uma M.; Tita, Alan T.N.; Silver, Robert M.; Mallett, Gail; Hill, Kim; Thom, Elizabeth A.; Wapner, Ronald J.; Rouse, Dwight J.; Saade, George R.; et al.
Abstract : OBJECTIVE: To evaluate characteristics associated with adverse outcomes in low-risk nulliparous women randomized to elective labor induction at 39 weeks of gestation or expectant management. METHODS: We conducted a secondary analysis of women randomized during the 38th week to induction at 39 weeks of gestation or expectant management. Deliveries before 39 weeks of gestation and those not adherent to study protocol or with fetal anomalies were excluded. A composite of adverse outcomes (perinatal death or severe neonatal complications), third- or fourth-degree lacerations, and postpartum hemorrhage were evaluated. Log binomial regression models estimated relative risks and 95% CIs for associations of outcomes with patient characteristics including randomly assigned treatment group. Interactions between patient characteristics and treatment group were tested. RESULTS: Of 6, 096 women with outcome data, 5, 007 (82.1%) met criteria for inclusion in this analysis. Frequency of the perinatal composite was 252 (5.0%), 166 (3.3%) for third- or fourth-degree perineal laceration, and 237 (4.7%) for postpartum hemorrhage. In multivariable analysis, intended labor induction at 39 weeks of gestation was associated with a reduced perinatal composite outcome (4.1% vs 6.0%; adjusted relative risk [aRR] 0.71; 95% CI 0.55–0.90), whereas increasing body mass index (BMI) was associated with an increased perinatal composite outcome (aRR 1.04/unit increase; 95% CI 1.02–1.05). Decreased risk of third- or fourth-degree perineal laceration was observed with increasing BMI (aRR 0.96/unit increase; 95% CI 0.93–0.98) and in Black women compared with White women (1.2% vs 3.9%; aRR 0.34; 95% CI 0.19–0.60). Increased risk of postpartum hemorrhage was observed in Hispanic women compared with White women (6.3% vs 4.0%; aRR 1.64; 95% CI 1.18–2.29). Patient characteristics associated with adverse outcomes were similar between treatment groups ( P for interaction >.05). CONCLUSION: Compared with expectant management, intended induction at 39 weeks of gestation was associated with reduced risk of adverse perinatal outcome. Patient characteristics associated with adverse outcomes were few and similar between groups. CLINICAL TRIAL REGISTRATION: ClinicalTrials.gov, NCT01990612. Abstract : Characteristics associated with adverse outcomes were few and similar between induction and expectant management, and induction at 39 weeks of gestation was associated with reduced adverse perinatal outcomes.